2013
DOI: 10.1042/bj20130490
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of cyclin G2 by insulin, IGF-I (insulin-like growth factor 1) and X10 (AspB10 insulin): role in mitogenesis

Abstract: The mechanisms whereby insulin analogues may cause enhanced mitogenicity through activation of either the IR (insulin receptor) or the IGF-IR (insulin-like growth factor 1 receptor) are incompletely understood. We demonstrate that in L6 myoblasts expressing only IGF-IRs as well as in the same cells overexpressing the IR, IGF-I (insulin-like growth factor 1), insulin and X10 (AspB10 insulin) down-regulate the mRNA expression level of the cell cycle inhibitor cyclin G2, as measured by qRT-PCR (quantitative rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Insulin is a prominent growth factor, but its molecular targets regulating the cell cycle are still poorly defined . The Rb–E2F1 complex plays a pivotal role in cell cycle progression.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Insulin is a prominent growth factor, but its molecular targets regulating the cell cycle are still poorly defined . The Rb–E2F1 complex plays a pivotal role in cell cycle progression.…”
Section: Discussionmentioning
confidence: 61%
“…However, depending on the cell type, the PI3K–Akt and Ras–ERK1/2 signaling pathways are likely to be involved to variable degrees . While the molecular pathways mediating insulin‐induced metabolic actions are well characterized, the mechanisms whereby insulin stimulates mitogenesis and regulates the cell cycle and G 1 /S progression remain to be fully clarified . Insulin signaling and action are also tightly monitored by negative regulators, including the molecular adapter growth factor receptor binding protein 14 (Grb14) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…FOXO also activates the cell cycle inhibitor cyclin G 2 (24). Moreover, insulin and IGF-I have been reported to down-regulate the expression of cyclin G 2 as part of their mitogenic effect (25). Hence, FOXOs are considered as tumor suppressors.…”
mentioning
confidence: 99%
“…Cyclin G2 was found to be markedly downregulated by insulin, insulin analogues and IGF-I in L6 myoblasts overexpressing the insulin receptor, as well as in several other cell types [ 98 , 99 ]. Overexpression of cyclin G2 inhibited cell proliferation induced by insulin, insulin analogues and IGF-I [ 99 ]. The use of specifi c inhibitors indicated that both the MAPK (mitogen-activated protein kinase) and the PI3K (phosphoinositide 3-kinase) pathways mediate the downregulation of cyclin G2.…”
Section: Cell Cycle Regulation By Rtksmentioning
confidence: 99%